Pengaruh Media Konkret terhadap Hasil Belajar IPA pada Siswa Kelas IV SDN Bencongan 6 Kabupaten Tangerang - Nurlaela, Eva; Magdalena, Ina; Unaenah, Een (FONDATIA, 2023)
The purpose of this study was to find out whether learning science in the experimental class was different from learning science in the control class. Control Group Design Not Equivalent to Quasi Experimental Design is the research methodology used. A procedure called sampling makes use of multiple samples. The population of this research is 70 students of class IV. 35 students from class IV B became the control group, while 35 students from class IV C became the experimental group. Data collection techniques include tests, observations, interviews, and documentation. It can be concluded from the posttest findings that tangible learning materials have an impact on science learning outcomes for fourth grade students at SDN Bencongan 6 based on statistical analysis using the t-test at a significance level = 0.05% obtained tcount (4.10) > ttable (1.99).